Maxims of Politeness Performed by Female Sellers at Traditional Market in Sumatera Barat - Ike Revita; Sofia Marwati; Ayumi Ayumi; Ainun Mardiah (Masyarakat Linguistik Indonesia Universitas Andalas, 2020)
This research is aimed at describing the maxims of politeness used by female sellers in a traditional market in Sumatera Barat. The research was conducted in one tradititonal market in Sumatera Barat, namely Batu Sangkar. The data are any utterances produced by female sellers in a traditional market in a traditional market in Batu Sangkar. The data were taken by the observational method with note-taking, recording, and interviewing techniques. The analysis was done by using the concept proposed by (Oktavianus & Revita, 2013; Leech, 1983). The result of the analysis was descriptively done and used the chart. The percentage was also used to identify the number of maxims that occurred. Having analyzed the data, it is found that the female sellers used four maxims in their interaction with the buyers. They are 1) tact, 2) agreement, and 3)modesty. There are two types of agreement between the sellers and the buyers, namely using 1) verbal and 2) non-verbal agreement. The non-verbal agreement is the indication of the insincerity of the sellers of the price bargained by the buyers. The sellers do not get much profit from the price offered by the buyers.